Unheard voices : a collection of narratives by black, gay and bisexual men - Johnson, Richard Greggory; Spencer, Kevin O.; Allen, Annie (Contemporary perspectives on LGBTQ advocacy in societies., 2021)
"The lives of African American gay men have greatly gone unnoticed in the American consciousness. Despite the fact that Black gay men have made great contributions to our global society. For example, James Baldwin served as a literature giant. Bayard Rustin was one of the key organizers of the 1963 March on Washington. Alphonso David is the first person of color to lead the HRC (Human Rights Campaign). The purpose of this book is to discuss the narratives of Black gay men. There is no doubt that American history has done a nonexistent job of portraying the lives of these Black gay men. Most of these lives have been relegated to the background of society. This book purposes to change that narrative by having 10 to 12 gentlemen, discuss their background and how it brought them to where they are in life now. The goal of this book is to also discuss the victory for each of authors"--